Business plan for a Caucasian cuisine restaurant in Prague - Abdurakhmanov, Said (2025)
With the growing popularity of ethnic cuisine in the Czech Republic, this study proposes a business plan for opening a Caucasian cuisine restaurant in Prague. The thesis is divided into two parts. The first part is devoted to the theoretical study of the concept and essence of the business plan and entrepreneurship, in general, as well as the methods of analysis used to develop a business plan. The second chapter offers materials on analysing the restaurant market in Prague and a business plan for a Caucasian restaurant.